Treatment isolated fungi from laboratory tools in some Baghdad hospitals by using biosynthesized nanoparticles - Tamkeen, Rayaheen Mohammed; Al-Bahrani, Rusol M. (Iraqi Journal of Science, 2019)
The study aims to biosynthesized of sliver nanoparticle from aqueous extract of olive leave and evaluate the effectiveness of the synthesis AgNPs against isolated fungi. The study mediating fifty samples were taken from various tools in laboratory from five hospitals in Baghdad. Four species of fungi were identified depending on the morphological and microscopic characteristics. The most common isolated fungi based on their frequency ratio were as follows Aspergillus niger 87.5%, Aspergillus flavus 62.5%, Aspergillus fumigatus 53.5% and Aspergillus nidulans 37.7%.The Biosynthesis of silver nanoparticle developed a rapid, eco-friendly and convenient green method for the stable silver nanoparticles (AgNPs) were synthesised with an average diameter of 30 ± 60 nm and like spherical in shape, using the aqueous solution of the Olive tree (Olea europaea) leaves extract.The reaction is carried out at 10-3M of silver nitrate. The AgNPs synthesized were confirmed by their change of color to (dark brown-grey). The characterization was studied using UV-Visible spectroscopy, Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). Inhibition effect of AgNPs against fungi has been studied using well diffusion method by studying the effect of different concentration (100, 75, 50 and 25). The results revealed that the AgNPs have considerable antifungal activity comparison with alcohol. The obtained results indicate that the highest level of inhibition zone was detected at the concentration of 100 µg/ml of AgNPs, where the inhibition zones are (23.33 ± 4.41) for A. flavus and the lowest level of inhibition zone was detected at the concentration 25 µg/ml of AgNPs ,where the inhibition zones are (6.00 ± 1.15) for A.nidalus. While using alcohol the highest level of inhibition zone was detected at the concentration of 100 µg/ml of Alcohol, where the inhibition zones are (12.33 ± 1.45) for A.nidalus, and the lowest level of inhibition zone was detected at the concentration 25 µg/ml of Alcohol ,where the inhibition zones are (4.67± 0.33) for A.flavus.